Beyond the Throwaway Society: Ordinary Domestic Practice and a Sociological Approach to Household Food Waste - Evans, David (Sociology (Oxford), 2012)
This article offers a sociological analysis of household food waste and its starting point is a critique of perspectives in which volumes of waste generation are used to infer the presence of a throwaway society. Drawing on broadly ethnographic examples, the analysis illustrates some of the ways in which the passage of 'food' into 'waste' arises as a consequence of the ways in which domestic practices are socially and materially organized. Specifically, attention is paid to: 1) routines of household food provisioning and the contingencies of everyday life; 2) the social relations manifest in the enduring convention of the family meal and; 3) the socio-temporal context of food practices. Taken together it is suggested that contemporary sociological approaches to home consumption, material culture and everyday life can usefully engage with public and policy concerns about the origins and consequences of food waste.